1975
DOI: 10.1007/bf01912460
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition kinetics of diethyl dithiocarbamate complexes of copper(II) and nickel(II)

Abstract: Thermogravimetric (TG), derivative thermogravimetric (DTG) and differential thermal analysis (DTA) curves of CuL~ and NiL2 (L-= diethyl dithiocarbamate anion) in air are studied. The main decomposition temperature ranges are: For CuL2, DTG 250--350 ~ DTA 300--320 ~ and for NIL2, DTG 290--390 ~ DTA 360--400 ~ Mass loss considerations at the main decomposition stages indicate conversion of the complex to sulphides. Mathematical analysis of TG data shows that first order kinetics are applicable in both cases. Kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Kinetic parameters calculated by employing the above equations are given in Table 3. reported value of 261.6 kJ mol-1 [17] for the decomposition of [Ni(S2CNEt2)2]. If we assume that the activation energy calculated with the Coats and Redfern method is nearly correct, then the activation energy calculated with the Horowitz and Metzger method has a 12% error.…”
Section: Decomposition Kineticsmentioning
confidence: 96%
See 2 more Smart Citations
“…Kinetic parameters calculated by employing the above equations are given in Table 3. reported value of 261.6 kJ mol-1 [17] for the decomposition of [Ni(S2CNEt2)2]. If we assume that the activation energy calculated with the Coats and Redfern method is nearly correct, then the activation energy calculated with the Horowitz and Metzger method has a 12% error.…”
Section: Decomposition Kineticsmentioning
confidence: 96%
“…where w, = total mass loss in the first stage and # = rate of heating (deg min -1 ~-=--"~ -6.4 obtained from the equation [17]:…”
Section: Decomposition Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…5) The entropy values for all degradation steps of all degradation steps of all complexes were found to be negative, which indicates a more ordered activated state that may be possible through the chemisorption of some decomposition products [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the large number of studies reported on the thermal analysis of coordination compounds, there are relatively few reports [1][2][3][4] on the calculation of the kinetic parameters and their relationship with the nature of the bonding. This may be due primarily to the uncertainties involved in the experimental measurements.…”
mentioning
confidence: 99%